Ability and Willingness as Sufficiency Conditions for Family‐Oriented Particularistic Behavior: Implications for Theory and Empirical Studies. (April 2014) - De Massis, Alfredo; Kotlar, Josip; Chua, Jess H.; Chrisman, James J.; Carsrud, Alan; Cucculelli, Marco
<x xml:space="preserve">Abstract</x> Distinguishing sufficient conditions from necessary conditions is crucial in both theoretical and empirical studies. We propose that the sufficiency condition for family involvement to produce family‐oriented particularistic behavior in a firm requires the presence of both ability and willingness. We demonstrate how the omission of this sufficiency condition in commonly used theoretical models employed to explain how family involvement affects firm behavior can result in theoretical limitations and empirical indeterminacy. Finally, we discuss how considering both ability and willingness can lead to better theory, more generalizable empirical findings, and help explain heterogeneity among firms with family involvement.